Peningkatan Kompetensi Penulisan Artikel Ilmiah Kepada Guru-Guru Di Wilayah Kabupaten Lombok Barat - Jihadil Qudsi; Andi Sofyan Anas; Akbar Juliansyah; Adam Bachtiar Maulachela; Raden Fanny Printi Ardi; Syahroni Hidayat; Danang Tejo Kumoro; Uswatun Hasanah; Sandi Justitia Putra (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
One of the consequences of teachers as functional positions is that teachers are required to carry out continuous professional development (CPD) so that teachers can carry out their duties and functions professionally. For this reason, teachers are required to have competency in researching and writing scientific papers in the form of books, modules and scientific articles. Writing scientific papers for teachers can serve as a reference / reference to increase insight or disseminate knowledge. This community service aims to equip teachers with scientific writing material, especially on scientific articles as well as provide assistance and consultation in writing scientific papers so that teachers are able to make scientific papers properly and correctly. The target of this service is partner schools from fellow institutes in West Lombok district, where the teachers who serve the school are expected to be able to produce a publication in a scientific paper.